Depression Rates After Facial Paralysis. Issue 2 (August 2019) - Saadi, Robert; Shokri, Tom; Schaefer, Eric; Hollenbeak, Christopher; Lighthall, Jessyka G.
Abstract : Introduction: Facial paralysis (FP) has many functional consequences with a large impact on daily life. Although an association with FP and depression has been observed and described in the literature, there are currently no large-scale studies to further validate this correlation. Our goal was to determine whether patients with FP become depressed at a higher rate compared with matched controls. Methods: We performed a retrospective cohort study using MarketScan Commercial Claims and Encounters Database by Truven Health. From the database, all inpatient and outpatient claims with International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes for FP and depression between 2005 and 2013 were extracted. Patients younger than 18 years were categorized as children and those 18 years or older as adults. Patients were subcategorized as having a history of depression if a diagnosis of depression preceding a diagnosis of FP was noted. We matched each patient to a control in the MarketScan database based on age, sex, and state of residence. We compared rates of depression between these patients and matched controls using conditional logistic regression. The method of Kaplan and Meier was used to estimate cumulative incidence curves of depression by each group. Results: Approximately 57, 941 patients were identified with International Classification of Diseases, Ninth Revision, codes for FP. Among children and adult patients without a diagnosis of depression before the index date for FP, 6.4% (285) and 9.7% (4733), respectively, had a diagnosis of depression within 2 years of the diagnosis of FP. Matched controls showed depression rates within 2 years of 3.9% for children ( P < 0.001) and 6.1% for adults ( P < 0.001). Conclusions: The present study adds to the current body of knowledge on FP and depression given its large sample size and analysis of adult and pediatric populations over 2 years. Indeed, we found that depression rates were significantly increased in both adults and children as compared with matched controls. Our results suggest a need for long-term depression screening in patients with FP.